Ocorrência de Spizaetus ornatus ornatus daudin. 1801, gavião-de-penacho (Falconiformes: Acciptridae) em Viçosa, Minas Gerais - Resende Monteiro , Alberto; de Mattos , Geraldo Theodoro (Revista Ceres, 2025)
The plumed hawk, Spizaetus o. ornatus Daudin, is recorded for the first time from Viçosa, Minas Gerais. This record is very important in ornithological studies because this species is rare in Brazil. Furthermore, there is no literature concerned with the biological and distributional attributes of this species in Brazil.